A critical discourse analytic approach to discursive construction of Islam in Western talk shows: The case of CNN talk shows. (January 2017) - Sharifi, Mahdi; Ansari, Nafiseh; Asadollahzadeh, Mina
The present research aimed at examining the discourse of CNN as a mainstream media, through the application of critical discourse analysis. The goal of this research was to uncover CNN's orientation in covering Muslim-related issues and to uncover how the elements described by van Dijk (2001) play their role in constructing the discourses of Islamophobic ideologies in CNN's talk shows. To this end, an analysis was conducted at two textual and contextual levels, including 34 programs, out of 50 GPS talk shows aired in 2013. The textual analysis was done regarding the three levels of meaning, argumentation, and style and the contextual analysis with regards to levels of access and participants. The findings revealed that CNN's representation of Muslim-related issues was biased and stereotypical at all levels; textual and contextual and the scope of the talk show was in line with the Islamophobic ideologies which prevail the Western media today.